2020
DOI: 10.1186/s12985-020-01388-w
|View full text |Cite
|
Sign up to set email alerts
|

AIV polyantigen epitope expressed by recombinant baculovirus induces a systemic immune response in chicken and mouse models

Abstract: Background: The protective efficacy of avian influenza virus (AIV) vaccines is unsatisfactory due to the presence of various serotypes generated by genetic reassortment. Thus, immunization with a polyantigen chimeric epitope vaccine may be an effective strategy for protecting poultry from infection with different AIV subtypes. Methods: Baculovirus has recently emerged as a novel and attractive gene delivery vehicle for animal cells. In the present study, a recombinant baculovirus BmNPV-CMV/THB-P10/CTLT contain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 53 publications
(80 reference statements)
0
3
0
Order By: Relevance
“…Finally, the antigen-displaying alternative baculoviruses are also being explored as another approach to developing vaccines for influenza. The HA incorporation into the baculovirus surface demonstrated an ability to elicit strong humoral and cell-mediated immunity that protected animals from the lethal challenge of influenza viruses (Prabakaran et al 2008;Prabakaran and Kwang 2014;Yu et al 2020).…”
Section: Influenza Vaccines and Diagnostic-reagent Productionmentioning
confidence: 99%
“…Finally, the antigen-displaying alternative baculoviruses are also being explored as another approach to developing vaccines for influenza. The HA incorporation into the baculovirus surface demonstrated an ability to elicit strong humoral and cell-mediated immunity that protected animals from the lethal challenge of influenza viruses (Prabakaran et al 2008;Prabakaran and Kwang 2014;Yu et al 2020).…”
Section: Influenza Vaccines and Diagnostic-reagent Productionmentioning
confidence: 99%
“…Th epitope TET (QYIKANSKFIGIT) was derived from the sequence of tetanus neurotoxin of Clostridium tetani . It was recently demonstrated that the incorporation of TET in a vaccine was able to induce humoral and cellular immunity in chickens and mice [ 10 ]; and was also utilized as marker to identify vaccinated from unvaccinated chickens [ 11 ]. Thus, induced immunity through this epitope may also enable the distinction of vaccinated chickens from infected ones.…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, Liu and colleagues ( 173 ) evaluated another BEVS-based H5 subunit vaccine (A/goose/Guangdong/1/96) and found that this vaccine could protect BALB/c mice as well as specific pathogen-free (SPF) and commercial broiler chickens, thus suggesting that it could be used as a candidate H5 influenza vaccine strain for humans and animals. Moreover, Yu and colleagues ( 174 ) used BEVS to construct a recombinant baculovirus vectored BmNPV-CMV/THB-P10/CTLT vaccine that contains the fused codon-optimized sequence of T lymphocyte epitopes (CTLT) from H1HA, H9HA, and H7HA AIV subtypes, and another fused codon-optimized sequence of Th and B cell epitopes (THB) from H1HA, H9HA, and H7HA AIV subtypes, which was then used to immunize mice and chickens. Their findings demonstrated that the vaccine could activate influenza virus-specific humoral and cellular responses in both species of the animal, suggesting that the vaccine could be used as a universal vaccine against different subtypes of AIV.…”
Section: Viral Vectored Influenza Vaccinesmentioning
confidence: 99%